Groundwater contamination by antibiotics: Review of sources, environmental factors and mobility - Quispe-Durand, Sahury Jellitza (2025)
Groundwater contamination by antibiotics poses an emerging risk to health and ecosystems due to their increasing use and persistence. The objective of this review was to identify the main sources, environmental factors, and mechanisms that determine the presence of these compounds in aquifers. The methodology was based on PRISMA principles, with a systematic search of the ScienceDirect and Scopus databases, resulting in the analysis of 60 articles published between 2015 and 2024. It was determined that wastewater treatment plants (WWTPs), together with agricultural, livestock, industrial, and hospital activities, are the predominant sources of input. Sulfonamides, tetracyclines, fluoroquinolones, and macrolides have been detected in aquifers in Asia, Europe, and America, in some cases exceeding ecological risk values. Their mobility and persistence depend on pH conditions, soil texture, dissolved organic matter (DOM), temperature and redox conditions, which control the processes of adsorption, leaching and degradation. In conclusion, this review shows that the presence of antibiotics in aquifers is explained by the complex interaction between anthropogenic sources and environmental factors.